Tuning of physical and electrochemical properties of nanocrystalline tungsten oxide through ultraviolet photoactivation. (10th May 2018) - Gayathri, P.T.G.; Sajitha, S.; Vijitha, I.; Shaiju, S.S.; Remya, R.; Deb, Biswapriya
Abstract: In this paper, we demonstrate the use of ultraviolet (UV, 365 nm) photoactivation to induce functional changes in the nanocrystalline tungsten oxide (n-WO3 ) surfaces. n-WO3 was initially synthesized by dissolving hydrated-WO3 powder in 10% H2 O2 with and without UV exposure. The photoactivation triggered homogeneous ligand-stripping in WO3 seeds that transformed the random-shaped clusters observed in the unexposed solution into a mono-modal distribution of spherical aggregates. These aggregates were electrophoretically collected as a coating that exposed to a second installment of UV soaking to explore photoactivation effects in the film state. A significant network densification is observed as photo-decomposition of bridging ligands facilitated direct interactions of surface dipoles in those films. Experiments showed that the photodecomposition mechanism predominantly depends upon the discharge of oxygen atoms localized on the material surface that can also create donor type oxygen vacancies. Electrochemical studies showed that the photoactivation led up to ∼2.8× enhancement in the surface donor density and considerably improved the interfacial charge transfer. The photoactivated electrodes exhibited up to ∼33% increment in the areal capacitance (Ca ) due to the increased number of active sites in the interface. Electrochromic (EC) response from the same electrodes produced ∼57% improvement in the optical density (OD). Highlights: UV photoactivation of n-WO3 dispersion triggered homogeneous ligand-stripping and alters their colloidal morphology. UV photoactivation process in film-state leads to significant network densifications in n-WO3 . The photo activation in films resulted insignificant increase of active surface sites to drive electrochemical reactions. The photoactivated electrodes exhibited up to ∼33% increment in the areal capacitance (Ca ). Electrochromic (EC) response from the same electrodes produced ∼57% improvement in the optical density (OD).